Citogenética e raça: um estudo em índios Kaingáng do Paraná - Junior, Euclides Fontoura da Silva; Cavalli, Iglenir João; Sbalqueiro, Ives José; Ribeiro, Lúcia Regina; Maia, Neria Amorim; Muniz, Elza Costa Netto (Acta Biológica Paranaense, 1988)
Citogenética e raça: um estudo em índios Kaingáng do Paraná